Thermoregulatory windows in Darwin's finches - Tattersall, Glenn; Chaves, J.; Danner, R. (Blackwell Publishing, 2018)
© 2017 The Authors. Functional Ecology © 2017 British Ecological Society Darwin's finches have been the focus of intense study demonstrating how climatic fluctuations coupled with resource competition drive the evolution of a variety of bill sizes and shapes. The bill, as other peripheral surfaces, also plays an important role in thermoregulation in numerous bird species. The avian bill is vascularized, while limbs have specialized vasculature that facilitate heat loss or heat conservation (i.e. they are thermoregulatory windows). The Galápagos Islands, home to Darwin's finches, have a hot and relatively dry climate for approximately half of the year, during which thermoregulatory windows (i.e. surfaces) could be important for thermoregulation and the linked challenge of water balance. We hypothesized that Darwin's finch bills have evolved in part for their role in thermoregulation, possibly co-opted, following adaptation for other functions, such as foraging. We predicted that bills of Darwin's finches are effective thermoregulatory windows, and that species differences in bill morphology, along with physiology and behaviour, lead to differences in thermoregulatory function. To test these hypotheses, we conducted a field study to assess heat exchange and microclimate use in three ground finch species and sympatric cactus finch (Geospiza spp.). We collected thermal images of free-living birds during a hot and dry season and recorded microclimate data for each observation. We used individual thermographic data to model the contribution of bills, legs and bodies to overall heat balance and compared surface temperatures to those from dead birds to test physiological control of heat loss from these surfaces. We derived and compared species-specific threshold environmental temperatures, which are indicative of a species’ thermally neutral temperature. In all species, the bill surface was an effective heat dissipater during naturally occurring warm temperatures. As expected, we found that finches controlled surface temperatures through physiology and that young birds had higher surface temperatures than adults. Larger bills contributed proportionally more to overall heat loss than smaller bills. We demonstrate here that related, sympatric species with different bill sizes exhibit different patterns in the use of these thermoregulatory structures, supporting a role for thermoregulation in the evolution and ecology of Darwin's finch morphology. A plain language summary is available for this article.